Neuroendocrine Tumors - Yao, James C.; Hoff, Paulo M.; Hoff, Ana O. (Current Clinical Oncology,, 2011)
New research has shown that neuroendocrine tumors are more common than previously thought.  Progress in our understanding of the molecular pathogenesis of these not-so-rare cancers has resulted in renewed interest in developing innovative therapeutic options.  In particular, novel molecular targeted agents have been shown to have significant anti-tumor activity, and integration of these therapies has led to critical advances in management. In this volume, an outstanding group of the world's leaders in the field have assembled to convey their knowledge of the epidemiology, biology, and management of all the major types of neuroendocrine tumors.  The book takes a multi-modality approach to understanding disease processes and therapeutics, including chapters on medical and surgical treatment as well as a chapter devoted to imaging.  Throughout, the authors emphasize recent advances in our understanding of molecular biology and the subsequent emerging therapeutic options.